Performance Measurement with SWOT Balanced Scorecard Analysis at Local Cooperatives in Minahasa Selatan District - Herke Francien Vernando Memah; Michel Jacson Nalawo Potolau (Media Ekonomi dan Manajemen, 2019)
This study aims to assess the performance of cooperatives and provide strategic recommendations that can help the Local Cooperative in carrying out its vision and mission. This study uses a descriptive research design. The results of the research work of KUD Karya Maesaan, Financial Perspective: Return on Investment (ROI) in 2014 is 1.31%, 2015: 0.86%, 2016: 2.15%. Return on Equity (ROE) in 2014 is 1.51%, 2015: 0.90%, 2016: 2.23%. Net Profit Margin in 2014 is 0.056, 2015: 0.137, 2016: 0.322. Cost Efficiency in 2016 is 97.09%, 2017: 95.57%. KSU Usaha Bersama: ROI in 2014 23.6%, 2015: 22.11%, 2016: 19.29%. ROE in 2014 was 36.77%, in 2015: 33.10%, in 2016: 31.45%. Net Profit Margin in 2014: 0.128, 2015: 0.148, 2016: 0.151. Cost Efficiency in 2016 is 98.62%, 2017: 96.75%. Customer Perspective: For the past 3 years, the number of customers of KUD Karya Maesaan and KSU Usaha Bersama always increases. The level of satisfaction of the customers for both cooperatives are in the level of very satisfied. Internal process perspectives: the processing time and delivery time for both cooperatives are running efficiently. In human resources perspective, both of the cooperative needs to increase the education level for their members and administrator.